223k views
4 votes
Whats the factored form of 6x 2 - 8x - 8 = 0

User Tagawa
by
5.5k points

2 Answers

2 votes

Answer:


2(3x-2)(x+2)=6x^2-8x-8

The factored form of
6x^2-8x-8=0 is
2(3x-2)(x+2)=0

Explanation:


6x^2-8x-8=0

The way the quadratic equation was given, we can't have a factored form in the format:
(ax-b)(cx+d)

First, divide both sides by 2


3x^2-4x-4=0

Now, it is about thinking. From the equation, we will get something in the format:
(ax-b)(cx+d)

Let's expand this:
(ax-b)(cx+d) = acx^2+adx-bcx-bd

From here, we can give some values for those variables, based on the quadratic equation
3x^2-4x-4=0:


(3x-b)(x+d) = 3\cdot 1\cdot x^2+3dx-b\cdot 1 \cdot x-bd= \boxed{3x^2+3dx-bx-bd}

Once we want the middle term to be -4 and bd to be 4, we can easily evaluate the other variables.


(3x-2)(x+2) = 3\cdot 1\cdot x^2+3(2)x-(2)\cdot 1 \cdot x-(2)(2)= \boxed{3x^2+6x-4x-4}

Therefore,


(3x-2)(x+2)=3x^2-4x-4

But we are not ready yet!

This is the factored form of
3x^2-4x-4=0, to get the factored form of the problem equation, just multiply the factored form we got by 2.


2(3x-2)(x+2)=6x^2-8x-8

User Vladimir Sotnikov
by
4.7k points
4 votes

Answer:

2(x -2)² = 0

Explanation:

2(x² - 4x - 4) = 0

2(x -2)² = 0

x = 2

User Damith Asanka
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.